EFFECTS OF MULCHES ON FLOWERING, FRUITING, YIELD AND PEST - DISEASE INCIDENCE OF TOMATO (LYCOPERSICON ESCULENTUM MILL.) - P. D. BHUJBAL; T. B. TAMBE; P. H. ULEMALE (The Bioscan, 2015)
The experiment was carried out at College of Agriculture, Latur. These sought to study the effects of different types of mulches on flowering, fruiting, yield and incidence of pest and diseases of tomato. (Lycopersicon esculentum Mill.) Var. Dhanashree. The flowering and fruiting attributes like lowest number of days for initiation of flowering of tomato (30.40 days), maximum number of flowers per plant (39.86), minimum number of days to first picking of tomato (83.40 days), maximum per cent of fruit set (70.36 %) and minimum per cent of fruit drop (12.51 %) was observed in treatment black colour on silver polythene mulch treatment. The yield attributes like maximum number of fruits per plant (26.66), maximum weight of fruit (72.40 g), maximum volume of fruit (77.33 ml), maximum yield of tomato (1.63 kg/plant) and (60.61 Mt/ha) and the pest-disease attributes like minimum leaf curl incidence (6.43 %), minimum spotted wilt incidence (2.26 %), minimum incidence of late blight (6.61 %) and minimum fruit borer incidence (5.06 %) was observed in black colour on silver polythene mulch treatment.